Ação da iluminação por led de alta potência sobre pseudomonas aeruginosa ufpeda 416 exposta à curcumina - Silva, Eduardo Cândido da (2022)
Light energy can be used to control microbial growth and Antimicrobial Photodynamic Therapy (PDTa) has the potential to use different natural compounds as photosensitizers. Curcumin is an example of a molecule on the rise in different areas from different perspectives. This study aimed to evaluate the effect of a natural photosensitizer (Curcumin) on planktonic cells and biofilm formation of Pseudomonas aeruginosa UFPEDA 416 at 480 nm emitted by a high frequency LED lamp. For this, in vitro assays were carried out to determine the Minimum Inhibition Concentration (MIC) and MBC (Minimum Bactericidal Concentration) of curcumin. MIC was detected at 0.63 μg/mL with no biocide effect. In the biofilm formation assay, P. aeruginosa UFPEDA 416 was exposed to curcumin (MIC concentration) and light energy (28.03 mW/cm2) for 20, 40, 60 and 120 minutes. Then, aliquots of 100 μL were transferred to microtubes containing Müeller-Hinton broth and incubated at 30ºC for 24 h. Biofilm was quantified using the violet crystal method. The results showed that there was a reduction in the ability of forming biofilm: from 40.8% in the first 20 minutes up to 11%, from 60 minutes, kept until the end. These results followed the decrease of planktonic cells, highlighting curcumin as potential photosensitizer.